Aplikasi Sistem Notifikasi Troubleshooting Jaringan (Sintar) Berbasis Web - Akhyar Lubis; Iskandar; Rio Septian Hardinata (STMIK Budi Darma, 2023)
Troubleshooting is a systematic process of identifying the source of a problem in order to find a solution. The troubleshooting approach is carried out to systematically identify the source of the problem, and network administrators will follow up on reports or complaints from service users. This research aims to quickly identify network issues with devices experiencing disruptions. The solution is to develop a web-based application to monitor network devices. This research is implemented by querying the host table with conditions of